2018
DOI: 10.3390/admsci8030046
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Employee Innovative Behavior and Thriving at Work: A Chinese Perspective

Abstract: Abstract:Drawing from the tenets of social cognitive theory, the present study examined the effect of thriving at work on innovation behavior via organizational support of innovation. The data were collected at three points in time from 402 participants occupying a variety of positions in Chinese organizations. Structural equation modeling and multilevel regression analysis results demonstrated that employees' thriving was positively related to organizational support of innovation, which in turn was positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 62 publications
(112 reference statements)
9
66
0
1
Order By: Relevance
“…Second, employees must be energetic to devote to implementing the new process, whereas psychological and social resources facilitate thriving and allow individuals' to be more innovative [3]. Previous empirical work supports the link between thriving and innovative behavior [8,12,18,19]. Thus, we hypothesize that H 1 : Thriving will be positively associated with innovative work behavior.…”
Section: Thriving and Innovative Behaviormentioning
confidence: 90%
See 2 more Smart Citations
“…Second, employees must be energetic to devote to implementing the new process, whereas psychological and social resources facilitate thriving and allow individuals' to be more innovative [3]. Previous empirical work supports the link between thriving and innovative behavior [8,12,18,19]. Thus, we hypothesize that H 1 : Thriving will be positively associated with innovative work behavior.…”
Section: Thriving and Innovative Behaviormentioning
confidence: 90%
“…In recent years, thriving as a proliferating construct has received a great deal of scholars' attention, and it is considered to be closely related to organizational outcomes such as better performance, employees' self-development, and work engagement [3,7,12]. However, it still needs more empirical development to distinguish and demonstrate that it is as an organizational construct [11].…”
Section: Thriving At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees' creativity has become a crucial factor for organizations to innovate products and services and compete against rivals (Riaz et al, 2018). According to Zhang (2010), managers play a key role in boosting the creative potential of subordinates.…”
Section: Conclusion and Implications For Managersmentioning
confidence: 99%
“…First of all, managers are advised to take part in empowering rather than in directive leadership. Riaz et al (2018) indicated that empowering leadership appears to provide employees with more motivation. This is consistent with the recommendation of Fritsch (2017), who claimed that individuals will be more productive and perform better if they are highly motivated.…”
Section: Conclusion and Implications For Managersmentioning
confidence: 99%